2021
DOI: 10.3390/children8010033
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effects of the Rapid Maxillary Expander on Temporomandibular Joint in Subjects Affected by Juvenile Idiopathic Arthritis: A Retrospective Study

Abstract: Background: In Juvenile Idiopathic Arthritis (JIA) temporo-mandibular joints are often affected causing skeletal and dental malocclusions. The most frequent condition is mandibular hypoplasia, that may be associated with maxillary hypoplasia. The aim of this retrospective case control study is to investigate the effects and the safety of rapid maxillary expansion (RME) in growing patients affected by JIA. It was evaluated whether RME could be performed without complications on TMJs of JIA patients using DC/TMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
0
22
0
6
Order By: Relevance
“…Despite these clinical alterations, recent studies have shown that JIA patients that ceased to show signs of active TMJ involvement for at least one year may find benefits from rapid maxillary expansion treatment, since resolving maxillary hypoplasia and impaired dental contacts may allow mandibular repositioning and condylar growth [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these clinical alterations, recent studies have shown that JIA patients that ceased to show signs of active TMJ involvement for at least one year may find benefits from rapid maxillary expansion treatment, since resolving maxillary hypoplasia and impaired dental contacts may allow mandibular repositioning and condylar growth [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Orthopedic maxillary expansion can be achieved using different fixed appliances that use deciduous or permanent teeth or miniscrews for support to transmit a lateral force to the two palatal processes of the maxillary bone, producing the splitting of the midpalatal suture and a certain amount of widening of the maxillary sutures [1]. The force is generated by a transversal screw that delivers a variable amount of force depending on several factors such as the activation protocol, its relative position in the palatal vault and its type of support.…”
Section: Introductionmentioning
confidence: 99%
“…The condylar surface damage is frequently clinically silent, i.e., it evolves without subjective or clinical expressions, which often causes a delay in diagnosis, Moreover, reliable monitoring during therapy is often hampered by the absence of pain and palpable swelling [14,15]. Symptoms, such as decreased mouth opening capacity (deviation of the mandible on mouth opening) and joint noises (crepitation and/or clicking), are not only usually noted late, but are also often underestimated [16].…”
Section: Introductionmentioning
confidence: 99%